(untitled) (The Journal of Plant Protection Sciences, 2021)
The whitefly, Dialeupora decempuncta it was felt necessary to study the field efficacy of Q u a i n t a n c e & B a k e r ( H o m o p t e r a : these insecticides against Dialeuropora Aleyrodidae), is a polyphagous pest, started decempuncta.causing severe damage to mulberry Morus The experiment was conducted at Central alba L since 1994. They suck leaf sap causing Sericultural Research & Training Institute, chlorosis, dryness of leaves, leaf curl and sooty Berhampore, West Bengal during August to mould disease and give effect to a culminating November 2009.